1989
DOI: 10.2307/2117753
|View full text |Cite
|
Sign up to set email alerts
|

Family Ties: Balancing Commitments to Work and Family in Dual Earner Households

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. American Sociological Association is collaborating with JSTOR to digitize, preserve and extend access to American Sociological Review. This paper examines the process by which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
210
0
23

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(252 citation statements)
references
References 27 publications
(15 reference statements)
10
210
0
23
Order By: Relevance
“…A third set of studies (Bielby and Bielby, 1989;Bruning and Snyder, 1983;Fry and Greenfeld, 1980), including another meta-analysis (Aven et al, 1993), report no sex differences in organizational commitment especially after controlling for job related variables, again with supportive evidence from individual studies conducted subsequently (Ngo and Tsang, 1998;Korabik and Rosen, 1995;Siguaw and Honeycutt, 1995). Further, a meta-analytic study by Mathieu and Zajac (1990) found that women are more affectively committed to the organization than men.…”
mentioning
confidence: 82%
“…A third set of studies (Bielby and Bielby, 1989;Bruning and Snyder, 1983;Fry and Greenfeld, 1980), including another meta-analysis (Aven et al, 1993), report no sex differences in organizational commitment especially after controlling for job related variables, again with supportive evidence from individual studies conducted subsequently (Ngo and Tsang, 1998;Korabik and Rosen, 1995;Siguaw and Honeycutt, 1995). Further, a meta-analytic study by Mathieu and Zajac (1990) found that women are more affectively committed to the organization than men.…”
mentioning
confidence: 82%
“…The identity formation model (Bielby and Bielby 1989) assumes that new ways of enacting motherhood and fatherhood lag considerably behind in historical perspective, as individual processes of reconstructing work and parenting identities are embedded in persisting traditional institutional contexts. The countries analysed in this book vary in the degree to which they support traditional gender ideologies.…”
Section: Doing Gender and 'Special Moneys' Among Dual-earner Parentsmentioning
confidence: 99%
“…While pregnancy and childbirth are recognized as a significant, identity-altering transition in women's lives and have received substantial scholarly attention, combining career and family has not been conceptualized in this way. Identity-based investigations of combining career and family have been grounded in the assumption that, for women, work and family represent separate, competing identities (Bielby & Bielby, 1989), assuming that women are oriented toward one identity domain over the other, rather than conceptualizing the crafting of a combined career and family life as identity work.…”
Section: Identity Work At Key Transitionsmentioning
confidence: 99%
“…The dominant competing identities perspective is supported by studies that indicate women are much more likely to make work-family identity trade-offs than men (Aryee & Luk, 1996;Bielby & Bielby, 1989;Rothbard & Edwards, 2003). For example, Lobel and St-Clair (1992) conceptualize and measure career identity salience and family identity salience as occupying opposite ends of a single spectrum.…”
Section: Identity Work At Key Transitionsmentioning
confidence: 99%